POTENSI TEH HIJAU (CAMELLIA SINENSIS L.) TERHADAP KUALITAS SPERMATOZOA DENGAN STRES OKSIDATIF: Sebuah Tinjauan Systematic Review - Chesya Raifela Devirza (2021)
Continuous exposure to xenobiotics may have an impact on the formation of free radicals, and disruption of the hormone system leading to decline in quality of spermatozoa and oxidative stress in cells. Antioxidants can play a role in preventing and improving these conditions. Green tea (Camellia sinensis L.) is one of the many natural antioxidants that contain catechin polyphenol compounds. This study aims to determine the potential effect of green tea on the quality of spermatozoa with oxidative stress. This research uses systematic literature review (SLR) method. Journal searches were carried out from August to November 2020 and were selected using the PRISMA-P method. The journal assessments were conducted using the Quality Assessment Criteria compiled by JBI (Joanna Briggs Institute). The results showed that there were six journals stating an increase in quantity and motility, four journals stating an increase in viability, four journals stating a decrease in abnormalities and one journal stating a decrease in motility of spermatozoa after green tea extract administration. Conclusion: Green tea contains catechin compounds which can be useful in improving the quality of spermatozoa with oxidative stress.